Dune‐like dynamic of Martian Aeolian large ripples. Issue 16 (30th August 2016) - Silvestro, S.; Vaz, D. A.; Yizhaq, H.; Esposito, F.
Abstract: Martian dunes are sculpted by meter‐scale bed forms, which have been interpreted as wind ripples based on orbital data. Because aeolian ripples tend to orient and migrate transversely to the last sand‐moving wind, they have been widely used as wind vanes on Earth and Mars. In this report we show that Martian large ripples are dynamically different from Earth's ripples. By remotely monitoring their evolution within the Mars Science Laboratory landing site, we show that these bed forms evolve longitudinally with minimal lateral migration in a time‐span of ~ six terrestrial years. Our observations suggest that the large Martian ripples can record more than one wind direction and that in certain cases they are more similar to linear dunes from a dynamic point of view. Consequently, the assumption of the transverse nature of the large Martian ripples must be used with caution when using these features to derive wind directions. Key Points: Martian large ripples dynamics are more similar to longitudinal dunes than impact ripples First evidence for longitudinal large ripple migration on Mars Martian large ripples consistently migrate in Gale Crater